Knowledge management in higher education: a meta-synthesis of success factors, challenges, and implementation strategies - Mohammad Hossein Zerafati; Reza Hosseinpour (مدیریت راهبردی دانش سازمانی)
Purpose: This study aims to conduct a comprehensive qualitative meta-synthesis of knowledge management implementation in higher education institutions, focusing on identifying critical success factors, challenges, and implementation strategies. The research seeks to develop an integrated framework that captures the multifaceted nature of knowledge management in academic settings while providing practical guidelines for successful implementation.Methodology: The study employs a systematic qualitative meta-synthesis methodology following Sandelowski and Barroso's (2006) seven-step approach. From an initial pool of 80 articles published between 2018 and 2023, nine high-quality studies were selected through rigorous inclusion criteria. The research utilized systematic database searches across Web of Science, Scopus, and Google Scholar. The selected studies were analyzed using qualitative content analysis to identify recurring themes, patterns, and relationships. The Critical Appraisal Skills Programme (CASP) was employed to ensure methodological rigor, and peer review was used to enhance the reliability of the findings.Findings: The meta-synthesis revealed five critical success factors for knowledge management implementation in higher education:1. Supportive organizational culture emerged as the most crucial factor, emphasizing the need for trust, transparency, and continuous learning values.2. Information technology infrastructure was identified as essential for facilitating knowledge storage, retrieval, and sharing.3. Senior management support was found to be vital for resource allocation and strategic alignment.4. Reward and motivation systems were recognized as crucial for encouraging knowledge-sharing behaviors.5. Flexible organizational structure was determined to be necessary for facilitating cross-departmental collaboration and knowledge flow.The study also identified significant challenges, including:- Resistance to change among academic staff- Lack of knowledge-sharing culture- Resource constraints (both financial and human)- Bureaucratic organizational structures- Limited understanding of knowledge management benefitsImplementation strategies were categorized into three main areas:1. Cultural interventions (fostering trust, promoting collaboration)2. Structural modifications (creating knowledge management roles, establishing communities of practice)3. Technological solutions (implementing knowledge management systems, developing digital repositories)The research culminated in developing a comprehensive conceptual model that illustrates the interrelationships between success factors, challenges, and implementation strategies in academic knowledge management.Research limitations: Several limitations should be considered:- The relatively small sample size of nine studies may not capture all relevant perspectives- Geographic concentration of studies in specific regions may limit global generalizability- Lack of access to raw data from primary studies restricted certain types of analysis- Temporal limitations of selected studies may not reflect the most recent developments- Methodological variations across studies complicated direct comparisonsThese limitations suggest opportunities for future research, including:- Longitudinal studies examining long-term impacts of knowledge management initiatives- Cross-cultural comparative studies of knowledge management implementation- Investigation of emerging technologies' impact on academic knowledge management- Studies focusing on knowledge management's role in achieving sustainable development goals- Research on the relationship between knowledge management and intellectual capital in universitiesPractical implications: The study provides several actionable recommendations for higher education institutions:1. Develop comprehensive knowledge management strategies aligned with institutional objectives2. Implement targeted training programs to enhance awareness and skills3. Design appropriate incentive systems to encourage knowledge sharing4. Review and modify organizational structures to facilitate knowledge flow5. Invest in suitable information technology infrastructure6. Create specialized knowledge management roles and teams7. Establish regular knowledge-sharing sessions across departments8. Develop knowledge repositories and information banks9. Implement mentoring programs for tacit knowledge transfer10. Regular assessment of knowledge management effectivenessThe findings emphasize the need for a holistic approach that addresses cultural, structural, and technological dimensions simultaneously. The study provides practical guidelines for academic leaders and administrators implementing knowledge management initiatives.Originality/value: This meta-synthesis offers several unique contributions to the field:1. Provides a comprehensive and integrated perspective on knowledge management in higher education by synthesizing recent qualitative research2. Develops a novel conceptual framework that captures the dynamic relationships between success factors, challenges, and implementation strategies3. Offers practical, evidence-based recommendations for academic institutions4. Identifies gaps in current understanding and suggests directions for future research5. Addresses the complex interplay between organizational culture, technology, and human factors in academic knowledge management6. Contributes to the theoretical understanding of knowledge management in educational contexts7. Presents a systematic analysis of implementation challenges and corresponding solutionsThe study's value lies in its synthesis of diverse perspectives and experiences, providing a robust foundation for both theoretical advancement and practical application in higher education knowledge management. It serves as a valuable resource for academic leaders, administrators, and researchers working to enhance knowledge management practices in higher education institutions.The findings underscore the importance of adopting a systemic, long-term approach to knowledge management implementation, recognizing that success requires careful attention to cultural, structural, and technological factors. This research contributes to both the theoretical understanding of knowledge management in academic settings and provides practical guidance for its implementation.